Bioadsorpsi Pb(Ii) Menggunakan Kulit Jeruk Siam (Citrus Reticulata) - Solika, Nafikatus; Napitupulu, Mery; Gonggo, Siang Tandi (Jurnal Akademika Kimia, 2017)
A research about the bioabsorption of Pb(II) using the tangerine peel (Citrus reticulata) has been done. The purpose of this study is to determine the optimum contact time of tangerine peel and to determine the pH of the tangerine peel on the adsorption power of Pb(II) in solution. The method used in this study was a laboratory experiment using the tangerine peel waste as the adsorbent of Pb(II). The concentration of Pb(II) adsorbed was measured using a spectrophotometer spectrodirect. The results showed that the optimum contact time of adsorption the metal ions Pb(II) was 60 minutes with the absorption efficiency of 96.19%. The pH optimum of adsorption of the metal ion Pb(II) was at pH 4.0 with the absorption efficiency of 93.05%.